Statin-naïve anti-HMGCR antibody-mediated necrotizing myopathy in China. (November 2018) - Jiao, Yuqiong; Cai, Shuang; Lin, Jie; Zhu, Wenhua; Xi, Jianying; Li, Jin; Yue, Dongyue; Zhang, Tiansong; Qiao, Kai; Wang, Yin; Zhao, Chongbo; Lu, Jiahong
Highlights: Statin-naive anti-HMGCR cases. Pattern of muscle MRI. Early-onset cases are severer. Abstract: This study aimed to clarify the phenotypes and therapeutic responses of statin-naïve anti-3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) antibody-mediated necrotizing myopathy. Anti-HMGCR antibodies were tested with ELISA methodology in the sera sample of 98 patients meeting the idiopathic inflammatory myopathy criteria and with negative anti-signal recognition particle (SRP) antibody. Twenty-one statin-naïve patients with anti-HMGCR antibody were detected (21.4%), with onset age from 6 to 67 years old. Proximal weakness and neck flexion weakness was the core neurological feature. The average maximal creatine kinase (CK) level was 7968.6 ± 4408.7U/L. Muscle MR imaging showed edema (88.2%), moderate or severe fatty replacement (70.6%) and muscle atrophy (88.2%) in lower limbs. Fatty replacement was significantly more prominent in the medial and posterior musculature than the anterior musculature (p = 0.0013). Seven (33.3%) patients were treated with mono-glucocorticoid, and thirteen (61.9%) patients needed adjuvant immunosuppressant. Eight (38.1%) patients experienced symptom relapse. The early-onset patients (<50 years old) were found with higher CK levels, shorter duration course, poorer response to adjuvant immunosuppressant and more recurrent weakness than the late-onset patients (≥50 years old). As a conclusion, Statin-naïve anti-HMGCR antibody-mediated necrotizing myopathy may not be rare. Compared with late-onset statin-naïve patients with anti-HMGCR antibody-mediated necrotizing myopathy, early-onset patients presented severer clinical features and worse therapeutic responses.